Pengaruh Penggunaan Media Pembelajaran Jeopardy terhadap Pemahaman Konsep Matematika Siswa Kelas XI MA YPKP Sentani - Dika Dewi; Nining Puji Lestari; Ulfah Sa'adah; Asep Rosadi; Prihaten Maskhuliah (Jurnal Pustaka Cendekia Pendidikan, 2026)
Students' low level of mathematical conceptual understanding remains a major challenge in mathematics learning, as classroom instruction is often characterized by limited interaction and repetitive learning activities. These findings highlight the need for instructional media that can foster students’ motivation, pasticipation, concentration, and active engagement in mathematics learning. This study aimed to examine the effect of Jeopardy learning media on the mathematical conceptual understanding of eleventh-grade students at MA YPKP Sentani and to determine the magnitude of its effect. This study employed a quantitative approach with a pre-experimental one group pretest-posttest design. The participants were 38 eleventh-grade students selected through purposive sampling. Data were collected using an essay test comprising eight questions on the topic of double-angle trigonometric formulas and were analyzed using descriptive and inferential statistics, including normality, linearity, heteroscedasticity, and hypothesis testing. The findings revealed that the mean score increased from 24.79 on the pretest to 89.55 on the posttest. Hypothesis testing showed that the calculated t-value (24.846) exceeded the critical t-value (2.026), indicating a statistically significant effect. Simple linear regression analysis produced the equation Ŷ = 24.789 + 64.763X with a coefficient of determination (R²) of 0.848. These findings indicate that the use of Jeopardy learning media contributed 84.8% to the improvement of students' mathematical conceptual understanding, while the remaining 15.2% was influenced by factors beyond the scope of this study.